Map of tamarisk occurrence in Landsat scenes across Colorado River Basin from 2005 to 2007 - Evangelista, Paul; Girma, Rebecca; Young, Nicholas (Colorado State University. Libraries, 2017)
An overview map of tamarisk location data between 2005-2007 that fell within WRS2 Landsat scene extents that overlap with the Colorado River Basin.
This was map was created in ArcMap v10.5. A portion of these data were used to develop maps of tamarisk occurrence within the Colorado River Basin (see Tamarisk Mapbook Atlas).
Users of these maps and other analysis products are solely responsible for interpretations made from these products. The Natural Resource Ecology Laboratory makes every effort to ensure this map is free of errors but does not warrant the map or its features are either spatially or temporally accurate or fit for a particular use. The Natural Resource Ecology Laboratory provides this map without any warranty, either express or implied.
Natural Resource Ecology Laboratory (NREL)
Keywords: Tamarisk; map; Landsat; scene; occurrence